Morphometric variation of the horseshoe crab Tachypleus gigas (Xiphosura: Limulidae) from the Banyuasin estuarine of South Sumatra, Indonesia - Fauziyah FAUZIYAH; APON Z. MUSTOPA; FATIMAH FATIMAH; ANNA I. S. PURWIYANTO; ROZIRWAN ROZIRWAN; FITRI AGUSTRIANI; WIKE A.E. PUTRI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fauziyah, Mustopa AZ, Fatimah, Purwiyanto AIS, Rozirwan, Agustriani F, Putri WAE. 2021. Morphometric variation of the horseshoe crab Tachypleus gigas (Xiphosura: Limulidae) from the Banyuasin estuarine of South Sumatra, Indonesia. Biodiversitas 22: 5061-5070. Morphological studies are essential for fish resource management, ecology, conservation, and stock assessment. This research was conducted to characterize the morphological variation of the coastal horseshoe crab (Tachypleus gigas) from the Banyuasin estuarine, South Sumatra, Indonesia. The body weight (BW), prosoma width (PW), carapace length (CL), telson length (TEL), and total length (TL) were measured for describing the morphometric variability of T. gigas. A total of 70 T. gigas (32 females and 38 males) were found using trammel net fishing and bottom gillnet during the survey. Multivariate and allometric methods analyzed their morphometric characters. Based on Kruskal- Wallis tests, the result showed a significant difference in somebody measurements (TL and CL) between males and females. The principal component analysis (PCA) results showed that all morphometric characters had a strong correlation in both sexes, so the first principal component (PC1) values were 92% and 72%. In comparison, the second principal component (PC2) values were 5% and 20% in females and males, respectively. The results of discriminant function analysis (DFA) suggested that only one (BW) of the five morphometric characters was significant in separating both sexes. Both sexes were also revealed variations in growth patterns based on the allometric analysis results. These results were expected to be used as a basis for managing the horseshoe crab population-based conservation.